THE EFFECT OF EXISTANCE, RELATEDNESS, GROWTH MOTIVATION AND PEER SOCIAL SUPPORT ON ADVERSITY QUOTIENT IN WORKING INDUSTRIAL ENGINEERING STUDENTS - Annastasia, Maudy; Rahayuningsih, Idha (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2021)
The problems experienced by students who study and work will certainly have an impact on achievement in lectures and work. Therefore, students need an adversity quotient to overcome this problem. One of the internal factors that influence the adversity quotient is motivation (existence, relatedness, growth). While the external factor that affects the adversity quotient is peer social support. This study aims to determine the effect of the level of motivation for existence, relatedness, growth, and the level of peer social support on the level of adversity quotient of working industrial engineering students. This research is a correlational study with a quantitative approach. Participants of 50 students were obtained by incidental sampling technique. The scale used in this study is a Likert scale with 4 answer choices. The validity test used is content validity while the reliability test uses Cronbach's alpha analysis. The data analysis technique used is nonlinear regression analysis. The results of this study indicate that the significance value of the motivational variable for growth in the relationship between existence is 0.495 > 0.05 then Ho is accepted and Ha is rejected and the significance value of the peer social support variable is 0.003 > 0.05 then Ha is accepted, Ho is rejected. The variable of growth motivation related to the existence and social support of peers contributed 44.5% to the adversity quotient variable. While the remaining 55.5% is influenced by other variables not examined. The benefit of this research is to add information on the development of psychology regarding the variables of adversity quotient, Motivation (existence, relatedness, growth), and peer social support. Limitations in this study are the minimum subject so that for further researchers are expected to add research subjects and can add independent variables.